The moderating role of purging behaviour in the relationship between sexual/physical abuse and nonsuicidal self-injury in eating disorder patients - Gonçalves, Sónia (2017)
This study sought to examine predictors of nonsuicidal self-injury (NSSI) in eating disorder patients and to evaluate the moderating role of purging behaviours in the relationship between a theorised predictor (i.e. sexual/physical abuse) and NSSI. Participants in this study were 177 female patients with eating disorders (age range = 14–38 years) who completed semistructured interviews assessing eating disorder symptoms and eating disorder-related risk factors (e.g. history of sexual and physical abuse, history of NSSI and feelings of fatness). Results revealed that 65 participants (36.7%) reported lifetime engagement in NSSI, and 48 participants (27.1%) reported a history of sexual/physical abuse. Early onset of eating problems, lower BMI, feeling fat, a history of sexual/ physical abuse and the presence of purging behaviours were all positively associated with the lifetime occurrence of NSSI. The relationship between sexual/physical abuse before eating disorder onset and lifetime NSSI was moderated by the presence of purging behaviours, such that the relationship was stronger in the absence of purging. These findings are consistent with the notion that purging and NSSI may serve similar functions in eating disorder patients (e.g. emotion regulation), such that the presence of purging may attenuate the strength of the association between sexual/physical abuse history (which is also associated with elevated NSSI risk) and engagement in NSSI behaviours. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.